Peacock, Francesca. Pure Wit: The Revolutionary Life of Margaret Cavendish. New York, Pegasus Books, 2024. 384 pp. ISBN 978-1-63936-603-3 - Gyenis, Dorina (FOCUS: Papers in English Literary and Cultural Studies, 2024)
The legacy of the seventeenth-century authoress Margaret Cavendish is increasingly well-known amongst literary and academic circles but, in terms of a mainstream presence or a place in the canon, she is still considered somewhat obscure. Recent publications, however, such as Francesca Peacock’s Pure Wit (2024) might change that soon. Peacock’s biographical work is certainly not the first to be ever written about the life of authoress and public figure Margaret Cavendish. In terms of style and content, Pure Wit follows in the footsteps of two major contributors to the topic, the first being Douglas Grant’s Margaret the First (1957), which was much later followed by Katie Whitaker’s Mad Madge (2002). Now, over twenty years later, Peacock intends to tackle the topic once again, most likely due to the current academic boom surrounding Cavendish. The book consists of fifteen chapters in total (including the introduction) that provide a chronological account of the life and death of the Duchess of Newcastle. The volume, apart from demonstrating the most significant events and achievements that occurred in her life, successfully presents them within the context of seventeenth-century England, making the book a worthwhile read for a wide audience.